The Android malware handbook : manual analysis and ML-based detection - Han, Qian (Research scientist); Tetali, Sai Deep; Mandujano, Salvador; Porst, Sebastian; Subrahmanian, V. S.; Xiong, Yanhai (No Starch Press, 2024)
"Explores the history of Android attacks and covers static and dynamic approaches to analyzing real malware specimens, machine-learning techniques to detect malicious apps, and how to identify banking trojans, ransomware, and SMS fraud"--